ANALYSIS OF THE INFLUENCE OF FINANCING GROWTH BASED ON USAGE IN ISLAMIC BANKING ON INDONESIAN ECONOMIC GROWTH - muhammad iman taufik (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2023)
This research aims to determine the influence of Islamic banking financing in the form of Working Capital, Investment, and Consumption on Indonesian economic growth. The research employs a descriptive quantitative approach, and multiple linear regression analysis technique is used for analysis. The research results show that partial financing of working capital and consumption has a significant effect on Indonesian economic growth, while investment financing does not affect Indonesian economic growth. Furthermore, simultaneously, Financing of Working Capital, Investment, and Consumption have an impact on the level of Indonesian economic growth